Characterization of children hospitalized with traumatic brain injuries after building falls - Kirsten V. Loftus; Tara Rhine; Shari L. Wade; Wendy J. Pomerantz (BMC, 2018)
Abstract Background Unintentional falls cause a substantial proportion of pediatric traumatic brain injury (TBI), with building falls carrying particularly high risk for morbidity and mortality. The cohort of children sustaining building fall-related TBI has not been well-examined. We sought to characterize children hospitalized with building fall-related TBIs and evaluate if specific factors distinguished these children from children hospitalized with TBI due to other fall mechanisms. We secondarily assessed if TBI severity among children injured due to a building fall varied between children from urban versus non-urban areas. Methods This was a secondary analysis of the Pediatric Health Information System (PHIS), an administrative database from pediatric hospitals. We identified children < 15 years old, hospitalized between 2009 and 2014, with an associated TBI-related diagnosis due to a fall as determined by International Classification of Diseases, Clinical Modification, Ninth revision (ICD9-CM) diagnosis codes. Urban versus non-urban status was determined using PHIS-assigned Rural-Urban Commuting Area codes. Injury severity (i.e. Injury Severity Score (ISS) and head Abbreviated Injury Scale (AIS) score) were calculated. Head AIS scores were dichotomized into minor/moderate (1-2) and serious/severe (3-6) for analysis. Frequencies, descriptive statistics, Chi-square analysis, and Mann-Whitney U analysis characterized populations and determined group differences. Results The study cohort included 23,813 children, of whom 933 (3.9%) fell from buildings. Within the building fall cohort, 707 (75.8%) resided in urban areas, 619 (66.3%) were male, 513 (55.0%) were white, and 528 (56.6%) had government insurance; the mean age was 3.8 years (SD 2.9). There was a larger proportion of children with serious/severe TBI among those injured from building falls relative to other falls (63.4% vs 53.9%, p <  0.01). Among children injured from building falls, those from non-urban areas were more likely to sustain a serious/severe TBI relative to urban children (58.9% vs 53.6%, p <  0.01). Conclusions Children hospitalized following buildings falls with TBI sustained more severe injuries relative to other fall types. Although a majority of children hospitalized with building fall related-TBIs were from urban areas, those from non-urban areas frequently sustained serious head injuries. Future research should target expanding prevention efforts to include non-urban areas.